Bubbles and crowding-in of capital via a savings glut - Marten Hillebrand; Tomoo Kikuchi; Masaya Sakuragawa (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2013)
This paper uncovers a novel mechanism by which bubbles crowd in capital investment. If capital is initially depressed by a binding credit constraint, injecting a bubble triggers a savings glut. Higher returns in a new bubbly equilibrium attract additional investors who expand investment at the extensive margin. We demonstrate that crowding-in through this channel is a robust phenomenon that occurs along the entire time path after bubbles are injected.
urn:nbn:de:swb:90-371625
Keywords: E21; E32; E44; 330; rational bubbles; savings glut; crowding-in; financial frictions